2009
DOI: 10.1099/ijs.0.000935-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic placement of the Cyrtolophosididae Stokes, 1888 (Ciliophora; Colpodea) and neotypification of Aristerostoma marinum Kahl, 1931

Abstract: The ciliate family Cyrtolophosididae Stokes, 1888 contains species that are poorly known from both the morphological and molecular perspectives. To further our understanding of this family, one species, Aristerostoma marinum Kahl, 1931, was redescribed. Cells in our population had a mean in vivo size of 15¾8 mm. There were six rows of somatic kineties, as well as six dorsal kinetids belonging to sparsely ciliated somatic kineties. The oral apparatus comprised a bipartite paroral membrane and four adoral organe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
33
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 37 publications
7
33
1
Order By: Relevance
“…The most diverse groups in the sampled marine biomes were oligotrichs, choreotrichs and oligohymenophoreans. Colpodeans, usually reported in freshwater and terrestrial environments, were also confirmed to be quite numerous, although the vast majority of colpodean sequences were assigned by EukRef‐Ciliophora to a single genus, Aristerostoma , which includes known marine species (Dunthorn et al ., ). In total, 26% of the HTS reads were classified to a higher degree of resolution (i.e., to less inclusive taxa) by EukRef‐Ciliophora as compared with SILVA (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The most diverse groups in the sampled marine biomes were oligotrichs, choreotrichs and oligohymenophoreans. Colpodeans, usually reported in freshwater and terrestrial environments, were also confirmed to be quite numerous, although the vast majority of colpodean sequences were assigned by EukRef‐Ciliophora to a single genus, Aristerostoma , which includes known marine species (Dunthorn et al ., ). In total, 26% of the HTS reads were classified to a higher degree of resolution (i.e., to less inclusive taxa) by EukRef‐Ciliophora as compared with SILVA (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…All colpodean species that have been described in enough detail have micronuclei (e.g., Bourland et al, 2013;Dunthorn et al, 2009;Foissner, 1993;Foissner et al, 2014;Quintela-Alonso et al, 2011). As micronuclei are only involved in sex (as far as we know), we propose that this cytological feature would have been lost over evolutionary time if the colpodeans are asexual.…”
Section: Genomic Data Support Secretive Sex In Colpodeansmentioning
confidence: 90%
“…On the other hand, the bipartition of the paroral membrane in cyrtolophosidids is unique within the class Colpodea, and it is thus considered as their most important apomorphic character (Foissner 1993), as also corroborated by molecular phylogenies (e.g. Dunthorn et al. 2009; Quintela‐Alonso et al.…”
mentioning
confidence: 98%
“…Paroral membrane. The paroral membrane is typically J‐shaped, dikinetidal and bipartited in the outgroup (Foissner 1993; Dunthorn et al. 2009).…”
mentioning
confidence: 99%